2020
DOI: 10.5194/egusphere-egu2020-21977
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do Statistical models capture magnetopause dynamics during sudden magnetospheric compressions?

Abstract: <p>Under steady-state conditions the magnetopause location is described as a pressure balance between internal magnetic pressures and the external dynamic pressure of the solar wind. The question is, does this approximation hold during more dynamic solar wind features?</p><p>Under more extreme solar wind driving, such as high solar wind pressures or strong southward-directed interplanetary magnetic fields, this boundary is significantly more compressed than in steady-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In Figure 3 the outermost L * values are not included as there are limited observations for L * > 6, particularly during the main phase. During storm time conditions, magnetopause shadowing reduces the number of closed drift paths (e.g., Staples et al., 2020) and the last closed drift shell is often within L * = 7 (Olifer, et al., 2018). Consequently, there are often no particles with closed drift paths in 6 ≤ L *<7 during geomagnetic storms.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 3 the outermost L * values are not included as there are limited observations for L * > 6, particularly during the main phase. During storm time conditions, magnetopause shadowing reduces the number of closed drift paths (e.g., Staples et al., 2020) and the last closed drift shell is often within L * = 7 (Olifer, et al., 2018). Consequently, there are often no particles with closed drift paths in 6 ≤ L *<7 during geomagnetic storms.…”
Section: Resultsmentioning
confidence: 99%
“…(1998) model has a precision of about 1 R E . This precision can be worse during strong or sudden magnetosphere compression events, the magnetopause being always closer to the Earth than the predicted one (Staples et al., 2020). During such events the distance to the magnetopause is overestimated by the model: EMIC might be even closer to the magnetopause than reported in previous sections.…”
Section: Discussionmentioning
confidence: 96%
“…This is in agreement with the study by Samsonov et al (2016) which found that accounting for a realistic ring current in global MHD brings values closer to the empirical MP models. However, as shown in Staples et al (2020), the validity of MP standoff distances as estimated by the empirical models during extreme events is questionable. Since the study does not employ direct comparisons with satellite crossings, a future extension of this work would compare modeled results directly against in-situ measurements from satellites like Cluster, THEMIS, MMS, or Geotail (e.g., Angelopoulos et al, 2009;Lin et al, 2010;Burch and Phan, 2016;Collado-Vega et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A performance analysis of many such models was presented by Lin et al (2010) to compare their model against a range of empirical models dating back to 1993. More recently, Staples et al (2020) conducted a thorough analysis of MPSD model performance, especially during extreme driving.…”
Section: Introductionmentioning
confidence: 99%